Variations in whole brain radiation therapy fractionation for brain metastases in Victoria. Issue 8 (21st June 2022) - Chee, Lessandra Yan Shan; Sia, Joseph; Milne, Roger L; Foroudi, Farshad; Millar, Jeremy L; Ong, Wee Loon
Abstract: Introduction: We aim to evaluate the use of different whole brain radiation therapy (WBRT) fractionation schedules for brain metastases (BM) in Victoria, and the factors associated with it. Methods: This is a population‐based cohort of patients who received radiation therapy for BM between 2012 and 2017, as captured in the Victorian Radiotherapy Minimum Dataset. We excluded patients with primary brain tumour and those who had 'prophylactic' intent treatment. The Cochran–Armitage test was used to evaluate changing trend in WBRT fractionation. Multivariate multinomial logistic regressions were used to evaluate factors associated with WBRT fractionation. Results: Of the 3111 patients who had WBRT, 1048 (45%), 1291 (42%) and 312 (13%) had ≤5, 6–10 and >10 fractions WBRT respectively. There was progressive increase in ≤5 fractions WBRT use over time, from 37% in 2012 to 50% in 2017 ( P ‐trend < 0.001). In multivariate analyses, increasing age, patients with gastrointestinal cancer, patients living in remote/regional areas and more recent treatment were associated with the use of shorter WBRT fractionation (≤5 fractions), while patients who had WBRT plus stereotactic radiosurgery, and those treated in private institutions were associated with the use of prolonged WBRT fractionation (≥6 fractions). Three hundred eighty‐nine (13%) patients died within 30 days of WBRT, of which 241 (64%), 119 (32%) and 17 (5%) had ≤5, 6–10 and > 10 fractions WBRT respectively. Conclusion: We observed large variations in WBRT fractionation that are associated with patient, tumour, treatment and institutional factors. It is important to continuously monitor and benchmark our practice in order to reduce potentially unwarranted variations.